Acacia hydaspica R. Parker ethyl-acetate extract abrogates cisplatin-induced nephrotoxicity by targeting ROS and inflammatory cytokines - Tayyaba Afsar (Nature Portfolio, 2021)
Abstract Cisplatin (CisPT) is a chemotherapeutic drug that outcomes in adverse effects. In this study, we examined the effect of A. hydaspica ethyl acetate extract (AHE) in an animal model of cisplatin-induced acute kidney injury (AKI). 36 male Sprague Dawley rats were used in the AKI rat model, and CisPT (7.5 mg/kg BW, i.p) single dose was given. In the pretreatment module, AHE (400 mg/kgBW/day, p.o) was given for 7 days before and after CisPT injection. While in the post-treatment group AHE was administered for 7 days after a single CisPT shot. The standard group received silymarin (100 mg/kg BW, p.o) for 7 days before and after CisPT injection. In HCT 116 tumor xenografts (n = 32) two groups of mice were pretreated with 400 mg/kg AHE orally for 7 days and two groups were treated with distilled water. On day 7 of pretreatment one distilled water and one AHE pretreated group were injected i.p with 15 mg/kg bw dose followed by another dose of CisPT 2 wk later. AHE groups were additionally treated with 400 mg/kg AHE for 3 days/week for 2 weeks. CisPT significantly deteriorated renal function parameters, i.e., PH, specific gravity, total protein, albumin, urea, creatinine, uric acid, globulin and blood urea nitrogen. CisPT treatment increased oxidative stress markers, while lower renal antioxidant enzymes. AHE pretreatment ameliorates significantly (p < 0.0001) CisPT-induced alterations in serum and urine markers for kidney function. Furthermore, AHE pretreatment more efficiently (p < 0.001) decreases oxidative stress markers, attenuate NF-κB, and IL-6 protein and mRNA expression by augmenting antioxidant enzyme levels compared to post-treatment. The histological observations verified the protective effect of AHE. In tumor xenograft mice, AHE treatment significantly reduced CisPT induced oxidative stress while it did not interfere with the anticancer efficacy of cisplatin as shown by significance (p < 0.001) decrease in tumor size after treatment. A. hydaspica AHE might provide a prospective adjuvant that precludes CisPT-induced nephrotoxicity without compromising its antitumor potential.